Transmitted Ultrasound Pressure Variation in Micro Blood Vessel Phantoms - Qin, Shengping (2008)
Silica, cellulose, and polymethylmethacrylate tubes with inner diameters of ten to a few hundred microns are commonly used as blood vessel phantoms in in vitro studies of microbubble or nanodroplet behavior during insonation. However, a detailed investigation of the ultrasonic fields within these micro-tubes has not yet been performed. This technical note provides a theoretical analysis of the ultrasonic fields within micro-tubes. Numerical results show that for the same tube material, the interaction between the micro-tube and megaHertz-frequency ultrasound may vary drastically with incident frequency, tube diameter, and wall thickness. For 10 MHz ultrasonic insonation of a polymethylmethacrylate (PMMA) tube with an inner diameter of 195 μm and an outer diameter of 260 μm, the peak pressure within the tube can be up to 300% of incident pressure amplitude. However, using 1 MHz ultrasound and a silica tube with an inner diameter of 12 μm and an outer diameter of 50 μm, the peak pressure within the tube is only 12% of the incident pressure amplitude, and correspondingly the spatial-average-time-average intensity within the tube is only 1% of the incident intensity.